Analysis of the Role of P4MI Sidoarjo in Case Labor Contract Violations in Malaysia - Adrian Agung Raharjo; Slamet Muliono Redjosari (Politeknik Siber Cerdika Internasional, 2025)
This study analyzes the role of the Indonesian Migrant Workers Protection Service Center (P4MI) Sidoarjo in handling work contract violations against Indonesian Migrant Workers (PMI) in Malaysia. This study uses a qualitative approach with in-depth interview methods with P4MI officers, former PMI victims of contract violations, and analysis of internal documents and relevant regulations. The findings show that P4MI Sidoarjo is quite responsive in receiving complaints and is able to carry out mediation in a neutral and inclusive manner. However, challenges such as limited human resources, pressure from placement companies, limited cross-border access, and weak post-case reintegration programs still hamper the effectiveness of comprehensive PMI protection. Based on the human security framework and Law No. 18 of 2017, this study emphasizes the importance of strengthening institutions, increasing the capacity of officers, and integrating cross-border and post-repatriation protection systems to ensure fair and sustainable protection for PMI.